2021
DOI: 10.48550/arxiv.2106.00079
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fundamental Challenges to Remote Sensing of Exo-Earths

Adiv Paradise,
Kristen Menou,
Christopher Lee
et al.

Abstract: Inferring the climate and surface conditions of terrestrial exoplanets in the habitable zone is a major goal for the field of exoplanet science. This pursuit will require both statistical analyses of the population of habitable planets as well as in-depth analyses of the climates of individual planets. Given the close relationship between habitability and surface liquid water, it is important to ask whether the fraction of a planet's surface where water can be a liquid, 𝜒 hab , can be inferred from observatio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…They remarked that longer, continuous observing periods will help with mapping. Indeed, clouds may have the largest impact on spectra variation (Paradise et al 2021), as we have also found in our simualtions. Additionally, Schwartz et al (2016) found that, at least theoretically, it should be possible to determine the obliquity of an exoplanet by observing at 2-4 different orbital phases.…”
Section: Challenges and Future Worksupporting
confidence: 83%
“…They remarked that longer, continuous observing periods will help with mapping. Indeed, clouds may have the largest impact on spectra variation (Paradise et al 2021), as we have also found in our simualtions. Additionally, Schwartz et al (2016) found that, at least theoretically, it should be possible to determine the obliquity of an exoplanet by observing at 2-4 different orbital phases.…”
Section: Challenges and Future Worksupporting
confidence: 83%
“…Proposed next-generation direct imaging missions might be capable of enough precision for the exo-cartography of small planets-solving the inverse problem of 2D albedo distributions from time-resolved light curves-which might discriminate between land and ocean surfaces (Cowan & Fujii 2018;Farr et al 2018;Lustig-Yaeger et al 2018;Aizawa et al 2020;Kawahara 2020). Interpretations of the data may remain highly model dependent and burdened by cloud removal, however (Paradise et al 2021;Teinturier et al 2022). Ocean fractions might also be discerned from near-infrared polarimetric observations (Takahashi et al 2021).…”
Section: Constraints From Astrophysical Datamentioning
confidence: 99%
“…Proposed next-generation direct imaging missions might be capable of enough precision for the exo-cartography of small planetssolving the inverse problem of 2D albedo distributions from time-resolved light-curves-which might discrim-inate between land and ocean surfaces (Cowan & Fujii 2018;Farr et al 2018;Lustig-Yaeger et al 2018;Kawahara 2020;Aizawa et al 2020). Interpretations of the data may remain highly model-dependent and burdened by cloud removal, however (Paradise et al 2021;Teinturier et al 2022). Ocean fractions might also be discerned from near-infrared polarimetric observations (Takahashi et al 2021).…”
Section: Constraints From Astrophysical Datamentioning
confidence: 99%